Strategi Komunikasi Politik Ketua DPRD DKI Jakarta pada Konstituen dengan Memanfaatkan Media Sosial Facebook - Fransisika Silolongan; Ambarwati Ambarwati; Novianty Elizabeth Ayuna (Syntax Idea)
Facebook social media plays a significant role in the political communication strategy of legislative members with their constituents. Legislative members can utilize the features of this social media platform to interact with their constituents and convey political messages. This study employs a qualitative approach with a descriptive analysis model and utilizes an interpretative paradigm. The data collection technique in this research involves structured interviews. The informants in this study consist of 4 members of the Jakarta Regional People's Representative Council (DPRD) from the Indonesian Democratic Party of Struggle faction and 2 social media observers. The conclusion of this research is that the political communication strategy employed by members of the Indonesian Democratic Party of Struggle faction in the Jakarta DPRD involves uploading content related to their daily activities as DPRD members through their respective Facebook accounts. The benefits that DPRD members gain by using the Facebook social media platform include gaining recognition among the broader public, receiving criticism and suggestions, comprehensively absorbing constituents' aspirations, and using it as a benchmark for problem-solving and improving their duties and responsibilities as DPRD members.